WANITA BEKERJA MENURUT ISLAM: ANALISIS GENDER - Endri Yenti (Universitas Islam Negeri Imam Bonjol Padang, 2011)
Women are part of a pluralistic society, he also became the figure of the man who brought the mission partners prosper earth so as to realize an empowerment within the scope of a more macro. With this cooperation, life can take place and walk upright, the community can develop and banner banner of truth can berkiba. Over the development period, the role of women is not just limited as a wife for her husband and mother to children. Women who used his fate depends only on the husband to meet his needs, it's been changed, not a few women who can meet even the existing kebutuhanya whose income exceeds the husband. Various artistic life began to open wide for women. Although there is no prohibition for women to work, but it should kind of work was not prohibited and do not lead to unlawful acts, such as travel day and night without a mahram or work in a place that happens ikhtilath (mixed up) between men and women. Indeed there is no proof that qath'i about illegitimate woman out of the house, but the scholars still place some conditions on the permissibility of women out of the house. Until the nature and the nature of women who actually stay awake. Keywords : Wanita bekerja, Islam, masyarakat dan memilih pekerjaanCopyright © 2011 by Kafa`ah All right reservedDOI : 10.15548/jk.v1i1.49